Evaluation of the External Radiation Effects of Fly Ash Added to Iraqi Concrete (مجلة المنصور, 2023)
Increased in treats in measuring radionuclides and radon concern tractions in fly ash, cement and other components of building products is due to concern of health hazard of naturally occurring radioactive materials. The current work focuses on studying the influence of fly ash (FA) on radon – exhalation rate (radon flux) from cementations material. The tests were carried out on cement past specimens with FA content. It is found that despite the (more than 3 times, compared with Portland cement). The radon – exhalation rate was found top significantly lower in concrete containing fly ash than in ordinary concrete